CORPORATION LEGAL LIABILITY IN CASES OF ENVIRONMENTAL POLLUTION - Syaharani, Syaharani (Communale Journal, 2024)
The economy is positively impacted by the industry's presence. However, it will also generate a waste product known as waste as part of the production process. This research examines the company's accountability for trash contamination in the surrounding environment. Article 88 of Law No. 11 of 2020 about Job Creation removes businesses' total obligation to be responsible. Law No. 32 of 2009 concerning Environmental Protection and Management are compared in this study to examine examples. This research employs a normative juridical approach. It is well known that the Job Creation Law itself modifies the absolute responsibility clauses that once tied companies under Law Number 32 of 2009 concerning Environmental Protection and Management. The study's findings suggest that administrative responsibility is the only corporate accountability for waste pollution that arises once absolute duty is removed.